2014
DOI: 10.1080/21670811.2014.937150
|View full text |Cite
|
Sign up to set email alerts
|

Theorizing Citizenship in Citizen Journalism

Abstract: New WalkLeicester LE1 7JA+44 (0)116 252 5294 vpc2@le.ac.uk 2 ABSTRACT Citizen journalism has become a prominent term referring to a variety of newsgathering and reporting practices conducted via a range of new digital technologies. The scholarly literature on citizen journalism, however, has tended to concentrate on its significance for journalism theory and practice whilst comparatively neglecting underlying questions about the theories of citizenship utilized within citizen journalism. This article examines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…not by professional journalists, can be considered as citizen journalist content (Wall, 2015). At the same time, it involves investigative and reporting activities that are aided by new digital technologies (Campbell, 2014). This may, however, include a wide variety of cases, including individuals who happen to be at the right place at the right time as well as frequent contributors, bloggers, or individuals acting like journalists despite lacking press credentials (Wall, 2019).…”
Section: What Is Their Purpose/role? (Purpose/role: Citizen Journalism)mentioning
confidence: 99%
See 1 more Smart Citation
“…not by professional journalists, can be considered as citizen journalist content (Wall, 2015). At the same time, it involves investigative and reporting activities that are aided by new digital technologies (Campbell, 2014). This may, however, include a wide variety of cases, including individuals who happen to be at the right place at the right time as well as frequent contributors, bloggers, or individuals acting like journalists despite lacking press credentials (Wall, 2019).…”
Section: What Is Their Purpose/role? (Purpose/role: Citizen Journalism)mentioning
confidence: 99%
“…There are several important aspects to be highlighted in terms of the relevance of this concept for the object of this study. Firstly, compared to traditional journalists, the motivation of citizen journalists typically exceeds merely reporting in order to bring social and political change (Campbell, 2014;Wall, 2019). This possibly relates to their dissatisfaction with traditional journalism and their performance and challenging the state of mainstream media corporations (Goode, 2009), as studies suggest a relation between lack of trust and seeking alternative sources of information (Kaufhold et al, 2010).…”
Section: What Is Their Purpose/role? (Purpose/role: Citizen Journalism)mentioning
confidence: 99%
“…Citizen journalism is not just contentious in relation to the professional versus amateur debate therefore, but also invites broader conceptual considerations of the term-such as the role of citizenship within citizen journalism (Campbell 2014) or what motivates such journalistic practices (Kim and Lowrey 2014). Furthermore, we know more about citizen journalism by some marginalised groups than others.…”
Section: Citizen Journalism and Social Changementioning
confidence: 99%
“…Additionally, the lack of relevant training, the news media change as described above and the recent global economic crisis contribute to an augmentation of the need for a collaborative media environment. At the same time, research has shown that the co-creation of news is explained by the development of participatory and grassroots journalism (Paulussen et al, 2007;Campbell, 2015;Wall, 2017;Gillmor, 2006) as well as the raising of innovative forms of news production (Lăzăroiu, 2014;Hermida, 2013) like mobile news and social networks (Westlund, 2015;Chan-Olmsted et al, 2013). Recent studies show that the interaction between new media teams (Lewis & Westlund, 2015) and the co-creative behavior of the team members (Agarwal & Barthel, 2015) enhances outcomes.…”
Section: Introductionmentioning
confidence: 99%